2017
DOI: 10.3802/jgo.2017.28.e83
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA methylation associated gene signatures in endometrial cancer via integrated analysis of DNA methylation and gene expression systematically

Abstract: ObjectiveEndometrial cancer (EC) is a common gynecologic cancer worldwide. However, the pathogenesis of EC has not been epigenetically elucidated. Here, this study aims to describe the DNA methylation profile and identify favorable gene signatures highly associated with aberrant DNA methylation changes in EC.MethodsThe data regarding DNA methylation and gene expression were downloaded from The Cancer Genome Atlas (TCGA) database. Differentially methylated CpG sites (DMCs), differentially methylated regions (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 35 publications
1
63
0
Order By: Relevance
“…Previous studies reported that TNXB was important for the tumorigenesis of lung adenocarcinoma 36 and identified TNXB as a novel deregulated gene with altered methylation in endometrial cancer. 25 In this study, we demonstrated that TNXB mRNA expression was downregulated in ESCC compared with adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Previous studies reported that TNXB was important for the tumorigenesis of lung adenocarcinoma 36 and identified TNXB as a novel deregulated gene with altered methylation in endometrial cancer. 25 In this study, we demonstrated that TNXB mRNA expression was downregulated in ESCC compared with adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 58%
“…However, the role of TNXB in tumorigenesis has not been well characterized. Previous studies reported that TNXB was important for the tumorigenesis of lung adenocarcinoma 36 and identified TNXB as a novel deregulated gene with altered methylation in endometrial cancer 25 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations